The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.ecoenv.2008.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Sequential toxicity identification evaluation (TIE) for characterizing toxicity of Venice Lagoon sediments: Comparison of two different approaches

Abstract: A toxicity identification evaluation phase-I (TIE-1) procedure was carried out on five pore water samples extracted from sediments of the Venice Lagoon previously investigated to assess both chemical contamination and toxic effects on the biota. Two different sequential TIE procedures were tested. A first sequence (TIE-1) provided for adding Na2S2O3, adding Na-EDTA, filtering, elution through a C18-SPE column and removing ammonia using the macroalgae Ulva rigida Agardh 1823, while a second procedure (TIE-2) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…Sediment TIEs have been successfully performed in many countries around the world over the last 20 yr [20][21][22][23][24][25][26][27][28]. The present study builds on a 2002 article [29] that analyzed the available set of data at the time (n ¼ 18).…”
Section: Introductionmentioning
confidence: 99%
“…Sediment TIEs have been successfully performed in many countries around the world over the last 20 yr [20][21][22][23][24][25][26][27][28]. The present study builds on a 2002 article [29] that analyzed the available set of data at the time (n ¼ 18).…”
Section: Introductionmentioning
confidence: 99%
“…They successfully identify compounds causing acute effects in more than 90 % of toxic samples analyzed (USEPA 1992;Thomas et al 2003) and have been applied to water and sediments in marine and freshwaters (Burgess et al 1995(Burgess et al , 1997Anderson et al 2010;Greenstein et al 2014) or effluents (Chan et al 2003;Yu et al 2003). Their utilization for water and sediment samples has identified cationic metals, nonpolar organics, and ammonia, among other contaminants (Schubauer-Beringan and Ankley 1991; Ankley and Schubauer-Beringan 1995;Van Sprang and Janssen 1997;Ho et al 2002;Araujo et al 2006;Buratini et al 2007;Nilin et al 2007;Picone et al 2008). In a recent study carried out at Funil reservoir, Rio de Janeiro State, Brazil, Matos et al (2014), have also identified cyanotoxins among the compounds involved in water toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The latter was often ignored by a conventional wastewater treatment plant. On the other hand, wastewater often contains a large number of chemicals, and not all of them are responsible for the observed toxicity; therefore, the toxicity identification evaluation (TIE) has been developed by the USEPA (USEPA, 1991, 1993a,b) and has been used for characterization and identification of key toxicants in various matrices, such as industrial wastewater, sediments, and leachates (Yang et al, 1999; Yu et al, 2003; Picone et al, 2009; Isidori et al, 2003). Key toxicants identified can be reduced or eliminated by overcoming the treatment deficiencies or applying special treatment methods (Jo et al, 2008).…”
mentioning
confidence: 99%